Molecular docking and glucosidase inhibition studies of novel N-arylthiazole-2-amines and Ethyl 2-[aryl(thiazol-2-yl)amino]acetates - Duarte, Vera (2017)
This study describes an efficient synthesis of a series of novel ethyl 2-[aryl(thiazol-2-yl)amino]acetates (4a-l) from N-arylthiazole-2-amines (3a-l). The reaction conditions were optimized and the best results were obtained when ethyl chloroacetate was used as alkylating agent and NaH as base in THF. alpha-glucosidase and beta-glucosidase inhibition activities of N-arylthiazole-2-amines (3a-l) and ethyl 2-[aryl(thiazol-2-yl)amino]acetates (4a-l) were determined, which revealed that most of the compounds showed high percentage inhibition towards the enzymes. Among the synthesized compounds, 4e appeared to have the highest inhibition towards alpha-glucosidase having IC50 value of 150.4 +/- 1.9 mu M which was almost two folds as compared to acarbose (336.9 +/- 9.0 mu M) taken as standard. Molecular docking of the compounds 3g, 3f, 4a, and 4e was also performed which showed their bonding modes to the enzyme's active sites via amino and acetate groups, respectively.